2016
DOI: 10.1179/1973947815y.0000000027
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of chemotherapy in epidermal growth factor receptor (EGFR) mutated metastatic pulmonary adenocarcinoma patients who had acquired resistance to first-line EGFR tyrosine kinase inhibitor (TKI)

Abstract: Pemetrexed-based combination chemotherapy is preferred before a more efficient treatment strategy is found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Recently, some studies enrolled patients who had tumors with EGFR mutation and received EGFR -TKI as the first-line therapy. Tseng et al 11 indicated that using cytotoxic chemotherapy as the second-line therapy resulted in a median PFS of 4.5 months and OS of 14.6 months. Similarly, this study showed that patients treated with cytotoxic chemotherapy as the second-line treatment after gefitinib failure had a median PFS of 4.3 months and OS of 14.6 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some studies enrolled patients who had tumors with EGFR mutation and received EGFR -TKI as the first-line therapy. Tseng et al 11 indicated that using cytotoxic chemotherapy as the second-line therapy resulted in a median PFS of 4.5 months and OS of 14.6 months. Similarly, this study showed that patients treated with cytotoxic chemotherapy as the second-line treatment after gefitinib failure had a median PFS of 4.3 months and OS of 14.6 months.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Indeed, Park et al 19 recently showed that pemetrexed used alone as a salvage drug after gefitinib failure provided significantly longer PPS than platinum-based doublet chemotherapy did (PFS: 4.2 months vs 2.7 months, P =0.008). Tseng et al 11 also demonstrated that chemotherapy with pemetrexed as the second-line chemotherapy for patients having acquired resistance to the first-line EGFR -TKI seemed to provide better PFS (4.7 months vs 3.3 months, P =0.62) and better OS (15.1 months vs 8.1 months, P =0.17) than chemotherapy without pemetrexed did, but the differences were nonsignificant and inconclusive. In our study population, chemotherapy with pemetrexed was associated with a significantly longer PFS and OS in patients with stage IV lung adenocarcinoma receiving salvage chemotherapy as the second-line treatment after gefitinib failure (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In two studies, 1 , 16 pemetrexed-based chemotherapy significantly extended PFS in EGFR -mutant NSCLC patients who failed first-line treatment with EGFR -TKIs (Park et al 1 : hazard ratio [HR] [95% CI] = 0.54 [0.34, 0.86], p =0.009; Yang et al 16 : 0.47 [0.26, 0.84], p =0.0101). Furthermore, Tseng et al 17 showed numerically longer PFS in NSCLC patients treated with pem regimens (median 4.7 months) compared to non-pem regimens (median 3.3 months). Overall, the weighted median PFS was numerically longer in patients treated with pemetrexed (5.09 months) than in patients receiving non-pem regimens (3.23 months; Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pemetrexed – either alone or in combination with other chemotherapy regimens – was effective among NSCLC patients with EGFR mutations who experienced resistance or disease progression after failure of EGFR -TKI treatment, with PFS ranging from 2.7 to 6.4 months and a weighted median PFS of 5.09 months ( Table 2 ). Three studies 1 , 16 , 17 directly compared the PFS data of pem regimens (n=148) versus non-pem regimens (n=97) in NSCLC patients with EGFR mutations who experienced resistance or disease progression after failure of EGFR -TKI treatment ( Table 2 ). In all three studies, median PFS was longer for the pem regimens as compared to the non-pem regimens ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…As histological transformation to small-cell lung carcinoma occurs during active treatment with targeted therapy, in dynamic progression it is recommended to do biopsy to capture these histological and phenotypic changes as this could impact the chemotherapy options [ 38 , 74 75 ]. Few studies suggest to continue chemotherapy after patients acquiring resistance [ 76 , 77 ]. Kuo et al reported higher remission rate (48.7% vs 21.4%), longer medium PFS (5.1 months vs 1.8 months) and medium OS (12.7 months vs 7 months) after receiving taxane-based chemotherapy than patients in nontaxane regimen [ 76 ] IMPRESS, a phase 3 randomized trial showed that progression-free survival was not prolonged in patients on continuation of gefitinib after disease progression compared to platinum-based doublet chemotherapy suggesting the later to be an gold-standard in such settings [ 78 ].…”
Section: Introductionmentioning
confidence: 99%